GAMBARAN TINGKAT DEPRESI PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS - Abdul Wakhid; Kamsidi Kamsidi; Gipta Galih Widodo (Jurnal Keperawatan Jiwa (JKJ): Persatuan Perawat Nasional Indonesia, 2018)
Pasien yang menjalani hemodialisis sebagian besar ketergantungan terhadap mesin hemodialisis yang mengakibatkan terjadinya perubahan seperti masalah finansial, kesulitan dalam mempertahankan pekerjaan, dorongan seksual yang menghilang, impotensi, dan berisikomengalami depresi.Tujuan penelitian ini untuk mengetahui gambaran tingkat depresi pasien gagal ginjal kronik yang menjalani hemodialisis di RSUD Kabupaten Semarang. Desain penelitian yaitu deskriptif korelatif dengan pendekatansurvei. Populasi penelitian 85 pasien yang menderita gagal ginjal kronik yang menjalani hemodialisis.Teknik sampling menggunakan quota sampling sehingga jumlah sampel penelitian yaitu 85 pasien gagal ginjal kronik yang menjalani hemodialisis. Pengumpulan data menggunakan kuesioner tingkat depresi. Analisis data menggunakananalisisunivariat. Hasil penelitian diperoleh sebagian besar pasien gagal ginjal kronik yang menjalani hemodialisisdepresi ringan sejumlah 41 orang (48,2%). Saran bagi RSUD Kabupaten Semarang untuk memberikan pelayanan keperawatan yang holistik pada pasien gagal ginjal kronik yang sedang menjalani hemodialisis. Kata kunci: Tingkat depresi, gagal ginjal kronik, hemodialisis DESCRIBE DEPRESSION LEVEL OF CHRONIC KIDNEY FAILURE UNDERGOING HEMODIALYSIS ABSTRACTThis research is motivated patients under going hemodialysis are largely dependent on hemodialysis machines resulting in changes such as financial problems, difficulty in keeping jobs, disappearing exualurges, impotence, and patient softenex perience self – conceptual disturbances as well as body image disturb ancesdue to the difficulty of accepting changes that result from failure kidney that  experienced resulting in depressed patients. The research aim is to describe depression level of chronic kidney failure under going hemodialysis ar Semarang Regency hospital. This research used descriptive correlative method with cross sectional approach. Population in this research were 85% of patients with chronic renal failure who under went hemodialysis at RSUD Semarang Regency. Sampling technique used sample quota. Data collection questionnaires used depressi on level sand self concept questionnaires. Analysis univariat was used in this analysis. The results of the study show that most patients with chronic renal failure under going hemodialysis experience mild depression as many as 41 people (48.2%). Suggestions to the hospital toteach patients to always optimistic to try new things, courageous, confident, enthusiastic, feeling self worth, dareto set a goal to live, behave and positively, and can be a reliable leader. Keyword: Depression level, chronic kidney disease, hemodialysis